2009
DOI: 10.1148/radiol.2532090027
|View full text |Cite
|
Sign up to set email alerts
|

Locally Advanced Rectal Cancer: Added Value of Diffusion-weighted MR Imaging in the Evaluation of Tumor Response to Neoadjuvant Chemo- and Radiation Therapy

Abstract: Adding DW MR imaging to conventional MR imaging yields better diagnostic accuracy than use of conventional MR imaging alone in the evaluation of CR to neoadjuvant CRT in patients with locally advanced rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
244
3
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 331 publications
(275 citation statements)
references
References 39 publications
18
244
3
10
Order By: Relevance
“…It is believed that the presence of microscopic residual tumor cell nests in fibrotic areas or in the mucinous subset is the main reason for indiscrimination of CR from near CR by DW-MRI (15). In our study, this hypothesis was supported by the determination that there was no relationship between post-CRT ADC values and SI changes with pRS in rectal tumors.…”
Section: Z=462)supporting
confidence: 67%
See 2 more Smart Citations
“…It is believed that the presence of microscopic residual tumor cell nests in fibrotic areas or in the mucinous subset is the main reason for indiscrimination of CR from near CR by DW-MRI (15). In our study, this hypothesis was supported by the determination that there was no relationship between post-CRT ADC values and SI changes with pRS in rectal tumors.…”
Section: Z=462)supporting
confidence: 67%
“…They stated that the mean ADC of the pCR group was significantly higher than that of the non-pCR group (1.62×10 -3 vs. 1.04×10 -3 mm 2 /s, respectively; P < 0.0001); however, an overlap of ADC values was observed in the two groups (15). In the current study, ADC measurements were taken from the normal rectal wall and rectal tumors.…”
Section: Z=462)mentioning
confidence: 58%
See 1 more Smart Citation
“…Differences between previous reported results and our findings are likely associated with differences in the study design (3,6,(14)(15)(16)(17)(18).…”
Section: Discussioncontrasting
confidence: 99%
“…The apparent diffusion coefficient (ADC) calculated from DW-MRI measurements may be used to quantify and express these properties. The majority of the studies have demonstrated that the pretreatment ADC is negatively correlated with response to treatment (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). It appears that necrotic areas with high pretreatment ADC values may be less sensitive to CRT.…”
Section: Introductionmentioning
confidence: 99%